Assessing the Impact of Heat Treatment of Food on Antimicrobial Resistance Genes and Their Potential Uptake by Other Bacteria-A Critical Review - Christian James; Ronald Dixon; Luke Talbot; Stephen J. James; Nicola Williams; Bukola A. Onarinde (MDPI AG, 2021)
The dissemination of antibiotic resistance genes (ARGs) is a global health concern. This study identifies and critically reviews the published evidence on whether cooking (heating) food to eliminate bacterial contamination induces sufficient damage to the functionality of ARGs. Overall, the review found that there is evidence in the literature that Antimicrobial Resistant (AMR) bacteria are no more heat resistant than non-AMR bacteria. Consequently, recommended heat treatments sufficient to kill non-AMR bacteria in food (70 °C for at least 2 min, or equivalent) should be equally effective in killing AMR bacteria. The literature shows there are several mechanisms through which functional genes from AMR bacteria could theoretically persist in heat-treated food and be transferred to other bacteria. The literature search found sparce published evidence on whether ARGs may actually persist in food after effective heat treatments, and whether functional genes can be transferred to other bacteria. However, three publications have demonstrated that functional ARGs in plasmids may be capable of persisting in foods after effective heat treatments. Given the global impact of AMR, there is clearly a need for further practical research on this topic to provide sufficient evidence to fully assess whether there is a risk to human health from the persistence of functional ARGs in heat-treated and cooked foods.